Operación y análisis de un reactor integrado anerobio-aerobio-anóxico para el tratamiento de aguas residuales - Plascencia Jatomea, Rigoberto (Universidad Autónoma Metropolitana, 2016)
Los reactores biológicos integrados son sistemas que permiten llevar a cabo procesos anaerobios y aerobios en un mismo reactor. Sin embargo, poco se sabe sobre su desempeño en el tratamiento de aguas residuales (municipales o industriales). En virtud de lo anterior, en esta tesis se estudiaron diversos factores que afectan el desempeño de un reactor biológico, tales como, la hidrodinámica, la transferencia de masa en biopelículas, así como diversas condiciones de operación del sistema; permitiendo la formulación de un modelo matemático integrado para predecir el comportamiento del reactor bajo nuevas condiciones de operación. El estudio de la hidrodinámica y la transferencia de masa del reactor integrado en columna permitieron el conocimiento del patrón de mezclado del reactor utilizando la técnica de la determinación de tiempos d e residencia. Esta técnica logró la identificación de problemas de estancamiento y canalización dentro del reactor. Estas desviaciones del patrón de flujo ideal fueron descritas correctamente mediante la utilización del modelo de celdas mezcladas, el cual es un modelo matemático que combina reactores ideales para describir el comportamiento de reactores reales. De acuerdo a este modelo, el reactor integrado en columna se ajusta a un reactor CSTR con problemas de canalización y estancamiento. Las desviaciones del patrón de flujo del reactor fueron identificadas y corroboradas mediante la utilización de la dinámica computacional de fluidos. Esta técnica computacional permitió conocer la localización de cada zona de flujo, pudiendo así darle un mayor peso al modelo de celdas mezcladas al poder diferenciar las características de cada zona en aspectos como; volumen de cada zona y el flujo que pasa a través de ellas. Una vez establecido el conocimiento de la hidrodinámica y la transferencia de masa del reactor, se procedió a su operación. El reactor integrado fue alimentado con agua residual del drenaje general de la Universidad Autónoma Metropolitana Unidad Iztapalapa, obteniendo eficiencias de degradación de materia orgánica (DQO) mayores al 83%, y la nitrificación con acumulación de nitrito permitiendo tener un efluente que pudiera servir para el proceso anammox. Una vez obtenida la información sobre la operación del reactor bajo diversas condiciones de operación (seis etapas), se procedió a la formulación del modelo matemático integrado (Integrated Carbon - Nitrogen Removal Model - ICNRM -). Este modelo considera el aspecto hidrodinámico, la trans ferencia de masa y reacción del reactor, permitiendo predecir el comportamiento del reactor con un error menor al 5% de acuerdo al proceso de validación del modelo. El modelo ICNRM permitió la propuesta de nuevas condiciones de operación que podrían permitir aumentar la eficiencia de degradación de materia orgánica a un 93% y un proceso de nitrificación con acumulación de nitrito estable, produciendo un efluente equimolar de amonio/nitrito adecuado para el proceso anammox. Esas simulaciones se realización siguiendo dos aspectos importantes, como son; la concentración de oxígeno y la mejora hidrodinámica. De acuerdo a esto, se encontró que la eficiencia del reactor podría ser aumentada mediante una mejora hidrodinámica, es decir, disminuir la canalización del reactor. En la búsqueda de estrategias para mejorar el patrón de mezclado del reactor, se hizo uso de la dinámica computacional de fluidos. Esta técnica permitió el diseño de dispositivos que permiten distribuir el flujo en todo el reactor, disminuyendo así los problemas de canalización. Acorde a los resultados obtenidos, se implementó un distribuidor de flujo denominado ―distribuidor de flujo de pared cónica‖, el cual permitió homogenizar la velocidad del fluido dentro del reactor, disminuyendo la relación de velocidad de la zona canalizada y estancada de 9 a 2.6.; Integrated reactors (IR) combining anaerobic, aerobic and nitrogen removal processes are a viable alternative to reduce operational costs and footprint compared to conventional wastewater treatment plants. An integrated bench scale (6.4 L) anae robic - aerob ic - anoxic column reactor (ICR) wa s develop ed to remove carbon and n itrogen compounds from sewage of Universidad Autónoma Metropolitana - Iztapalapa campus. The ICR is comprised of an up - flow anaerobic sludge blanket reactor (UASB), a membrane aerated biofilm reactor (MABR) and a denitrifying biofilm reactor (DNB). The global COD removal efficiency (η C - Global ) is ~82% at hydraulic retention time (HRT) of 8.4 h. The partial nitrification (PN) process is obtained with an ammonia/nitrite ratio (R a/ n ) of 4. The experimental data was used to calibrate and validate an integrated carbon - nitrogen removal model (ICNRM), in order to determine operating conditions for the improvement of the ICR performance, considering the hydrodynamic profile and reaction kinetics. A good agreement between the measured and modeled results is obtained with a least square error function ( S ) lower than 0.09. The model predicts that the COD removal efficiency at the MABR (η C - MABR ) and nitrite accumulation at the DNB are influen ced by the volumetric oxygen transfer coefficient ( k L a ) and oxygen concentration, respectively. The optimal operation zone for η C - MABR >90% and R a/n of 1.32 were reached for k L a between 1.26 to 1.36 1/h, and an inlet DO concentration of 1.5 to 1.6 mg/L resp ectively, standing out the importance of calibrating hydrodynamic behavior and kinetics. The central part of the integrated reactor, the membrane - aerated biofilm reactor (MABR) is a promising technology for wastewater treatment, especially for simultaneous organic and nitrogen removal. The knowledge of mass transfer phenomena induced by flow velocity and flow pattern is required in order to improve the reactor design and the pollutants removal efficiency. Tracer experiments and residence time d istribution (RTD) theory were us ed to characterize the flow in a special MABR oxygenating from the membrane side and from the liquid side . The liquid phase flow patterns were investigated by means of tracer pulse stimulus - response technique using dextran blue as model tracer. RTD curves were analyzed by cold - model tests (axial dispersion model ADM, tanks in series model TIS and mixing cell model MCM). T he detailed flow pattern of the reactor was obtained from computational fluid dynamic (CFD) simulation. According to experimental results of RTD studies and CFD simulation, the flow patterns were demonstrated to be analogous to completely mixed flow with d eviations of the ideal hydrodynamic behavior; stagnant zones (low fluid velocity) in 85% of its volume, being the remainder a channeling trouble (high fluid velocity). These deviations were quantitatively described (macromixing level - global mixing) with a minimum quadratic error function value of (S) 0.01. The local mixing flow pattern (micromixing level) obtained by CFD allowed determining the location of each zone; the stagnant zone is situated in the area where membranes are located; therefore it is poss ible to assume that degradation reactions of pollutants would take place in this area. MABR are gradually adapted to water treatment trains so its hydraulic profile directly affects the pollutant removal performance. The goal of this work was to develop a geometry design of inlet flow distributors of the MABR using Computational Fluid Dynamics (CFD). The new distributor geometry was experimentally evaluated with RTD experimental curves using the stimulus - response technique and approximated with the mixing cell model ( M CM) and by solving the hydrodynamic Navier – Stokes (NS) equation for laminar flow and mass transpor (convection – diffusion equation ) equations using computational fluid dynamics (F - tracer RTD method). Two sets of RTD experiments (common and new inlet flow distributors) in MABR were carried out. The volumetric flows (Q) employed were from 03.6 to 10 mL/min . The new inlet flow distributor (conical wall flow distributor) had a more homogeneous velocity field in the entire reaction zone (membrane zone) , as shown by MCM values lower than those obtained with the common MABR (without flow distributor) . The RTD curves obtained with Comsol Multiphysics 4.3 b are in agreement with RTD experimental curves reinforced the data obtained by the MCM . The operation of the integrated column reactor allowed the acquisition of experimental data under different operational conditions, enabling the appropriate development and validation of an integrated mathematical model (hydrodynamic - mass transfer - reaction ). This model could predict the behavior of the reactor with an error of <5%, demonstrating the feasibility of the use of this model to predict the reactor behavior. According to model simulations, this system can be improved in design aspects and experime ntal conditions in order to establish a nitrification process with nitrite accumulation to obtain a suitable stoichiometry ratio by manipulating the reaction time, dissolved oxygen and the improve ment of hydrodynamic behavior (reduction of the channeling zone).